Introduction to cyber-warfare a multidisciplinary approach - Shakarian, Paulo (Morgan Kaufmann Publishers, an imprint of Elsevier, 2013)
Cyber Warfare conducted by organizations such as Anonymous and LulzSec and by nation states such as China, China, India, Iran, North Korea and the United States (Stuxnet) has become a global problem threatening governments, corporations and individuals. According to a recent analysis the global market for Cyber Warfare consulting, product development and protective services will reach a value of $15.9 billion in 2012. This in-depth text on cyber warfare written by experts on the front lines, explores the cutting edge world of cyber-warfare through the use of recent case studies such as cyber-attack conducted by large, powerful, non-state hacking organizations such as Anonymous and LulzSec and cyber-espionage and exploitation attempts that are sponsored by nations, such as China, Iran and North Korea and the recent Stuxnet attack. These topics and other s are discussed not only from a computer security perspective but also from multi-disciplinary approach including policy, military, sociological, and scientific aspects. . Provides a multi-disciplinary approach to Cyber Warfare analyzing the information technology, military, policy, social, and scientific issues that are in play. . Presents detailed case studies of cyber-attack including inter-state cyber-conflict (Russia-Estonia), cyber-attack as an element of an information operations strategy (Israel-Hezbollah,) and cyber-attack as a tool against dissidents within a state (Russia, Iran) . Explores cyber-attack conducted by large, powerful, non-state hacking organizations such as Anonymous and LulzSec . Covers cyber-attacks directed against infrastructure such including but not limited to water treatment plants, power-grid and a detailed account on Stuxent
Includes bibliographical references and index
Keywords: HISTORY / Military / Strategy; Computer crimes; Cyberterrorism; Data protection; Information warfare; Information warfare -- Case studies; Cyberspace -- Security measures; Fallstudiensammlung